Os impactos da utilização da internet e outras tecnologias da informação sobre o setor industrial: uma análise de empresas de manufatura do estado de São Paulo - Graeml, Alexandre Reis (2004)
This research project intended to bring light to the way manufacturing organizations use the Internet and other information technologies in order to add value to their customers and/or reduce costs. Special attention is given to the virtualization of products and services that companies provide to their customers and to the virtualization of business processes, including the relationship with suppliers and other business partners. The study was based on survey data, obtained from 665 manufacturers from the state of Sao Paulo, Brazil. The analysis was performed using quantitative methods.